Cover Image. (6th April 2020) - Hu, Qing‐Qing; Wang, Qian; Luo, Yu‐Kun; Li, Ying‐Ying; Ma, Ming‐Xiang; Xu, Fu‐Fang; Yang, Jun; Wei, Rong
Abstract : The cover image is based on the Research Article Measurement of the polarization‐ and orientation‐dependent scalar, vector, and tensor light shifts in 87Rb using the near‐resonant, stimulated Raman spectroscopy by Qing‐Qing Hu et al., https://doi.org/10.1002/jrs.5821 .